Assessment of Effectiveness of Supply Chain Operations on Ecological Safety Assurance Tools of Dairy Herd Reproduction - Natalia N. Karzaeva; Olga I. Solovyova; Anna Yu.Voronina (International Journal of Supply Chain Management, 2019)
In the modern research, the assessment of effectiveness of introduction and application of technologies that minimize negative impact on the region ecology is carried out by boundaries dividing of ecological and industrial systems. In this research supply chain operation effects proposed to assess the impact of mechanisms for ensuring ecological safety based on integrational approach to determination of boundaries of ecological and industrial systems, and identification of ecological safety objects. The article substantiates the possibility of recognition of farm animals as ecological safety objects. Their dualistic nature is revealed as the biological resources of the system and an integral part of the natural environment. The methods used by specialists for the economic evaluation of the ecological safety tools application are analyzed and, proposed to use the differences between costs of its acquisition, use and expenses occurred when ignore it as an indicator of effective using of a specific tool for ensuring ecological safety. The article presents the results of the experience on the use of herbal medicine